Scale inhibition material and preparation method thereof

By adopting a multi-layer scale-resistance material with a columnar particle structure, the stacked structure and particle size gradient are used to adjust the release rate of scale-resistance active components, the problem of uneven efficiency of complex scale-resistance materials during use is solved, and a wider application scenario is achieved.

CN119638088AActive Publication Date: 2025-03-18JOMOO KITCHEN & BATHROOM
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411817526.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-18
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

In use, complex scale-resistant materials have problems such as insufficient scaling efficiency in the early stage, excessive scaling efficiency in the later stage and excessive consumption speed, and the release speed of the scale-resistant active ingredients is difficult to effectively control.

Method used

The scale-resisting material with a columnar particle structure is laminated in sequence from inside to outside along the radial direction. The first layer is columnar and the remaining layer is an annular structure. The mass proportion of the scale-resisting active components in each layer structure is greater than or equal to 45%. In the radial direction gradually away from the first layer structure, the average particle size of the scale-resisting active components of the outer layer structure is smaller than the average particle size of the inner layer structure.

Benefits of technology

It achieves the smooth release of effective components in scale-resistant materials, solves the problems of insufficient scale-resistant efficiency in the early stage and excessive consumption speed in the later stage, and broadens the scope of use and application scenarios of complex scale-resistant materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638088A_ABST
    Figure CN119638088A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of scale inhibition materials, in particular to a scale inhibition material and a preparation method thereof, and aims to solve the problems of insufficient early-stage scale inhibition efficiency, too high later-stage scale inhibition efficiency, too high consumption speed and the like of complexing scale inhibition materials in related technologies. The columnar particles are of a multi-layer structure which is sequentially stacked from inside to outside in the radial direction of the columnar particles. The first-layer structure is columnar, the other layers are of annular structures, and the next-layer structure wraps the circumferential surface of the previous-layer structure; each layer of structure comprises a polymer substrate and scale inhibition effective components dispersed in the polymer substrate; the scale inhibition effective components are soluble in water, the scale inhibition effective components are powdery, and in any two adjacent layer structures in the radial direction gradually away from the first layer structure, under the same composition proportion, the average particle size of the scale inhibition effective components of the outer layer structure is smaller than that of the scale inhibition effective components of the inner layer structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of scale-inhibiting material manufacturing, and in particular to a scale-inhibiting material and a preparation method thereof. Background Art

[0002] At present, the anti-scaling principles of anti-scaling materials are generally divided into physical principles and chemical principles. Physical principle-based anti-scaling modes include electromagnetic field anti-scaling, alloy anti-scaling, displacement anti-scaling, isolation anti-scaling, etc. Chemical principle-based anti-scaling modes include dissolution-type anti-scaling, precipitation-type anti-scaling, complexation-type anti-scaling, etc.

[0003] In various anti-scaling modes, each has its own advantages and disadvantages to a greater or lesser extent. Among them, the complex anti-scaling mode generally uses liquid complex anti-scaling agents or salt glass anti-scaling materials. The liquid complex anti-scaling agents dissolve quickly and are consumed quickly when used. They need to be used with a controller and are difficult to use in daily life. Salt glass anti-scaling materials are slightly soluble glass complexes composed of polyphosphates and polysilicates. Since these materials have been sintered into a glass-like state, the effective anti-scaling ingredients are released slowly when used. A large amount of material is required to effectively treat high-hardness, high-water-level water bodies. Moreover, they are very easy to agglomerate after drying after wetting, which affects replacement and use.

[0004] Therefore, the release speed of the effective scale-inhibiting ingredients of the complex scale-inhibiting materials is the most critical technology, which is not only related to the physical form of the scale-inhibiting materials, but also to the specific surface area of ​​the scale-inhibiting materials, etc. For granular scale-inhibiting materials, as they are dissolved and consumed, the ratio of their specific surface area to volume becomes larger and larger. As the material is consumed, the smaller its volume is, the faster the effective ingredients are released, which eventually leads to problems such as insufficient scale-inhibiting efficiency in the early stage, and excessively high scale-inhibiting efficiency and excessive consumption in the later stage. Summary of the invention

[0005] Based on this, some embodiments of the present application provide a scale inhibitor material, which, when used, can solve the problems of the complex scale inhibitor material in the related technology, such as insufficient scale inhibition efficiency in the early stage, too high scale inhibition efficiency in the later stage and too fast consumption rate, thereby solving the problem that the release speed of the effective scale inhibitor ingredients of the complex scale inhibitor material in the related technology is difficult to effectively control, and broadens the use scope and application scenarios of the complex scale inhibitor material; in addition, some embodiments of the present application also provide a preparation method of the scale inhibitor material.

[0006] In a first aspect, a scale-inhibiting material is provided, wherein the scale-inhibiting material is a columnar particle, and the columnar particle has a multi-layer structure stacked in sequence from the inside to the outside along its radial direction; the first layer structure is a columnar structure, and the remaining layers are annular structures, and the latter layer structure is coated on the circumference of the former layer structure;

[0007] Each layer structure includes: a polymer substrate and an anti-scaling effective component dispersed in the polymer substrate;

[0008] Among them, the scale inhibitory effective ingredient is soluble in water, the mass proportion of the scale inhibitory effective ingredient in each layer structure is greater than or equal to 45%, the scale inhibitory effective ingredient is in powder form, and in the radial direction gradually away from the first layer structure, in any two adjacent layer structures, at the same composition ratio, the average particle size of the scale inhibitory effective ingredient in the outer layer structure is smaller than the average particle size of the scale inhibitory effective ingredient in the inner layer structure.

[0009] Optionally, the anti-scaling active ingredient includes: calcium polyphosphate and polycarboxylate zinc powder dispersed in the calcium polyphosphate.

[0010] Optionally, the antiscaling material satisfies at least one of the following conditions:

[0011] (1) The materials for preparing the polymer substrate include: PE;

[0012] (2) In each layer structure, the mass proportion of the polymer substrate is 42% to 55%, the mass proportion of the zinc polycarboxylate is 10% to 20%, and the balance is the calcium polyphosphate;

[0013] (3) The average particle size of the polycarboxylate zinc powder is 15 μm to 25 μm.

[0014] Optionally, the columnar particle comprises: a first columnar structure, a first annular structure and a second annular structure sequentially stacked along the radial direction thereof, wherein the first annular structure is coated on the circumference of the first columnar structure, and the second annular structure is coated on the circumference of the first annular structure;

[0015] In the first columnar structure, the average particle size of the scale-inhibiting effective component is 70 μm to 75 μm, in the first annular structure, the average particle size of the scale-inhibiting effective component is 60 μm to 65 μm, and in the second annular structure, the average particle size of the scale-inhibiting effective component is 50 μm to 55 μm.

[0016] Optionally, the columnar particles are cylindrical, the diameter of the first columnar structure is 1.1 mm to 1.5 mm, the thickness of the first annular structure is 0.1 mm to 0.15 mm, and the thickness of the second annular structure is 0.1 mm to 0.15 mm;

[0017] Optionally, the diameter of the first columnar structure is 1.3 mm, the outer diameter of the first annular structure is 1.6 mm, and the outer diameter of the second annular structure is 1.9 mm.

[0018] Optionally, in the first columnar structure, the first annular structure and the second annular structure, the mass proportion of the zinc polycarboxylate powder is 11.3%, the mass proportion of the calcium polyphosphate is 44.3%, and the mass proportion of the polymer substrate is 44.4%; or,

[0019] In the first columnar structure, the first annular structure and the second annular structure, the mass proportion of the zinc polycarboxylate powder is 19.6%, the mass proportion of the calcium polyphosphate is 37.8%, and the mass proportion of the polymer substrate is 42.6%; or,

[0020] In the first columnar structure, the first annular structure and the second annular structure, the mass proportion of the zinc polycarboxylate powder is 10.5%, the mass proportion of the calcium polyphosphate is 36.4%, and the mass proportion of the polymer substrate is 53.1%; or,

[0021] In the first columnar structure, the first annular structure and the second annular structure, the mass proportion of the polycarboxylate zinc powder is 14.5%, the mass proportion of the calcium polyphosphate is 38.0%, and the mass proportion of the polymer substrate is 47.5%.

[0022] In a second aspect, a method for preparing a scale inhibition material is provided, comprising:

[0023] S11, preparing a plurality of raw materials for scale inhibitors; each raw material for scale inhibitors is a mixture of polymer-based particles and effective scale inhibitor ingredients, the effective scale inhibitor ingredients are soluble in water, and the mass proportion of the effective scale inhibitor ingredients in each raw material for scale inhibitors is greater than or equal to 45%, the effective scale inhibitor ingredients are in powder form, and at the same composition ratio, the average particle sizes of the effective scale inhibitor ingredients in any two raw materials for scale inhibitors are different from each other;

[0024] S12. Add multiple portions of raw materials for scale inhibition materials into different chambers of a multilayer extruder according to the different particle sizes of their respective scale inhibition effective ingredients, and prepare columnar particles by co-extrusion and cutting; along the radial direction of the columnar particles, the columnar particles include a multilayer structure stacked in sequence from the inside to the outside; in the multilayer structure, the first layer structure is columnar, and the remaining layers are annular structures, and the latter layer structure is coated on the circumference of the former layer structure; in the radial direction gradually away from the first layer structure, in any two adjacent layer structures, the average particle size of the scale inhibition effective ingredient of the outer layer structure is smaller than the average particle size of the scale inhibition effective ingredient of the inner layer structure.

[0025] Optionally, the multilayer extruder includes a plurality of heating chambers, wherein the outlet of the first heating chamber is cylindrical, the outlets of the remaining heating chambers are coaxially arranged with the outlet of the first heating chamber, and the outlet of the subsequent heating chamber is arranged around the outlet of the previous heating chamber; S12, comprising:

[0026] Adding a plurality of raw materials for the scale-inhibiting material into a plurality of heating chambers arranged in sequence from the first heating chamber of the multilayer extruder according to the average particle sizes of the respective scale-inhibiting effective components from large to small, and co-extruding the molten materials in each heating chamber through the screw in each heating chamber, and obtaining a strip material after cooling;

[0027] The strip material is cut into sections along the length direction of the strip material to obtain the columnar particles.

[0028] Optionally, S11 includes:

[0029] preparing calcium polyphosphate monomer;

[0030] The calcium polyphosphate monomer and the zinc polycarboxylate powder are mixed and sintered to copolymerize the calcium polyphosphate monomer to obtain a block polymer, wherein the zinc polycarboxylate powder is dispersed in the block polymer;

[0031] The block polymer is crushed into a plurality of powdered anti-scaling active ingredients, wherein the average particle sizes of any two of the powdered anti-scaling active ingredients are different from each other;

[0032] A plurality of the powdered antiscaling active ingredients are mixed with a plurality of granular materials of the polymer base contained in the raw material for the antiscaling material, respectively, to prepare a plurality of the raw materials for the antiscaling material.

[0033] Optionally, the preparation method satisfies at least one of the following conditions:

[0034] (1) The co-extrusion temperature is 140°C to 230°C;

[0035] (2) The sintering process is performed at a temperature of 800°C to 850°C and for a time of 20h to 25h;

[0036] (3) The average particle sizes of the plurality of powdered antiscaling active ingredients are 50 μm-55 μm, 60 μm-65 μm and 70 μm-75 μm respectively;

[0037] (4) The average particle size of the polymer substrate particles is 20 μm to 25 μm.

[0038] The beneficial effects of the above-mentioned antiscaling material and preparation method thereof are as follows:

[0039] By setting the scale inhibition material as a multi-layer structure stacked in sequence from the inside to the outside along the radial direction of the columnar particles, the first layer structure is columnar, and the remaining layers are annular structures. When it is used for scale inhibition, the scale inhibition effective ingredient is soluble in water, and because the mass proportion of the scale inhibition effective ingredient in each layer structure is greater than or equal to 45%, therefore, as the scale inhibition effective ingredient dissolves, the polymer substrate will be peeled off and dissolved in the water. Therefore, the effective scale inhibitors in each layer structure of the scale inhibitor material can be released at a certain speed under the dissolution of the scale inhibitor material, and as the dissolution is consumed, the specific surface area to volume ratio of the effective scale inhibitor material becomes larger and larger. At this time, since in the radial direction gradually away from the first layer structure, in any two adjacent layers, at the same composition ratio, the average particle size of the effective scale inhibitor components of the outer layer structure is smaller than the average particle size of the effective scale inhibitor components of the inner layer structure, therefore, as the dissolution is consumed, the average particle size of the effective scale inhibitor components of the scale inhibitor material becomes larger, thereby effectively reducing the release rate of the effective scale inhibitor components, and then effectively balancing the release rates of the effective scale inhibitor components in the early and late stages of the use of the scale inhibitor material, so that the effective scale inhibitor components in the scale inhibitor material can be released smoothly in the early and late stages of use, solving the problems of insufficient early scale inhibition efficiency, excessively high late scale inhibition efficiency and excessive consumption speed of the complex type scale inhibitor materials in the related art, thereby solving the problems of difficult to effectively control the release speed of the effective scale inhibitor components of the complex type scale inhibitor materials in the related art, and broadening the scope of use and application scenarios of the complex type scale inhibitor materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 A schematic flow chart of a method for preparing a scale-inhibiting material provided in an embodiment of the present application;

[0041] Figure 2 This is a graph showing the change in phosphorus dissolution in the test water sample of the scale inhibition material provided in Example 1 and Comparative Example 1 of the present application during the entire water flow process. DETAILED DESCRIPTION

[0042] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.

[0043] Unless the context requires otherwise, throughout the specification and claims, the term "including" is to be interpreted as an open, inclusive meaning, that is, "including, but not limited to". In the description of the specification, the terms "one embodiment", "some embodiments", "exemplary embodiments", "exemplarily" or "some examples" and the like are intended to indicate that specific features, structures, materials or characteristics associated with the embodiment or example are included in at least one embodiment or example of the present disclosure. The schematic representation of the above terms does not necessarily refer to the same embodiment or example. In addition, the specific features, structures, materials or characteristics may be included in any one or more embodiments or examples in any appropriate manner.

[0044] Exemplary embodiments are described herein with reference to cross-sectional views and / or plan views that are idealized exemplary drawings. In the drawings, the thickness of layers and regions are exaggerated for clarity. Therefore, variations in shape relative to the drawings due to, for example, manufacturing techniques and / or tolerances are conceivable. Therefore, the exemplary embodiments should not be interpreted as being limited to the shapes of the regions shown herein, but include shape deviations due to, for example, manufacturing. For example, an etched region shown as a rectangle will typically have curved features. Therefore, the regions shown in the drawings are schematic in nature, and their shapes are not intended to illustrate the actual shape of regions of the device, and are not intended to limit the scope of the exemplary embodiments.

[0045] In this document, "for example", "such as", "example", "for example", etc. are used for descriptive purposes, indicating that the previous and subsequent different technical solutions are related in terms of the content covered, but should not be understood as limiting the previous technical solution, nor can they be understood as limiting the scope of protection of this document. In this document, unless otherwise specified, A (such as B) means that B is a non-limiting example of A, and it can be understood that A is not limited to B.

[0046] In this article, "optionally", "optional", and "optional" mean optional, that is, any one of the two parallel options of "yes" or "no". If there are multiple "options" in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "option" is independent.

[0047] Herein, descriptions such as "optionally contain", "optionally include", etc., mean "contain or not contain". "Optional component X" means component X exists or does not exist, or means containing or not containing the component X.

[0048] In this document, the terms "first", "second", etc. in "the first aspect", "the second aspect", etc. are used for descriptive purposes only and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features.

[0049] It should be noted that when an element is referred to as being "fixed to" or "disposed on" another element, it may be directly on the other element or there may be a central element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be a central element at the same time. The terms "vertical", "horizontal", "upper", "lower", "left", "right" and similar expressions used herein are for illustrative purposes only and are not intended to be the only implementation method.

[0050] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0051] In this article, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0052] In this document, "at least one" means more than one, such as one, two and more than two. "Multiple" or "several" means at least two, such as two, three, etc.

[0053] Herein, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values ​​within the numerical interval is considered to be continuous and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when a numerical interval only refers to integers within the numerical interval, including the two endpoint integers of the numerical range, and each integer between the two endpoints, is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined. In other words, unless otherwise specified, the numerical ranges disclosed herein should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows broadly including numerical interval types such as percentage intervals, ratio intervals, and ratio intervals.

[0054] In this article, when it comes to percentage concentration, unless otherwise specified, it refers to the final concentration. The final concentration refers to the proportion of the added component in the system after the addition of the component.

[0055] In this article, if there are multiple steps involved in the method flow, unless there is a clear different description in this article, there is no strict order restriction for the execution of these steps, and they can be executed in other orders than described. Moreover, any step can include multiple sub-steps or multiple stages, and these sub-steps or stages are not necessarily executed at the same time, but can be executed at different times, and their execution order is not necessarily sequential, but can be executed in turn, alternating or simultaneously with other steps or parts of sub-steps or stages of other steps.

[0056] In view of the problems in the related art that the scale inhibition efficiency of the complex type scale inhibition material is not enough in the early stage, the scale inhibition efficiency is too high in the later stage and the consumption rate is too fast, and the release speed of the scale inhibition effective components of the complex type scale inhibition material is difficult to effectively control, the specific implementation method of the present application is described as follows:

[0057] In the first aspect, some embodiments of the present application provide a scale-inhibiting material, which is a columnar particle, and the columnar particle has a multi-layer structure stacked in sequence from the inside to the outside along its radial direction; the first layer structure is columnar, and the remaining layers are annular structures, and the latter layer structure is coated on the circumference of the previous layer structure. Each layer structure includes: a polymer substrate and a scale-inhibiting effective component dispersed in the polymer substrate; wherein the scale-inhibiting effective component is soluble in water, and the mass proportion of the scale-inhibiting effective component in each layer structure is greater than or equal to 45%, the scale-inhibiting effective component is in powder form, and in the radial direction gradually away from the first layer structure, in any two adjacent layers, at the same composition ratio, the average particle size of the scale-inhibiting effective component of the outer layer structure is smaller than the average particle size of the scale-inhibiting effective component of the inner layer structure.

[0058] The scale-inhibiting active ingredient is soluble in water, and the mass proportion of the scale-inhibiting active ingredient in each layer structure is greater than or equal to 45%. Therefore, as the scale-inhibiting active ingredient dissolves, the polymer substrate is peeled off and dissolved in the water, so that the scale-inhibiting active ingredient can be continuously released into the water, complexing calcium ions in the water, etc., so as to play a scale-inhibiting role. The scale-inhibiting active ingredient can exemplarily include a complexing scale-inhibiting material.

[0059] The anti-scaling active ingredient is in powder form. In each layer structure, the particle size of the anti-scaling active ingredient may be uneven, some large and some small. Here, the average particle size is used to characterize the relative size of the particle sizes in different layer structures.

[0060] Here, in different layer structures, the particle size of the scale inhibitory effective ingredients can be regarded as increasing or decreasing in equal proportion. Therefore, the average particle size can reflect the overall particle size of the scale inhibitory effective ingredients in each layer structure. For example, in the radial direction gradually away from the first layer structure, in any two adjacent layer structures, at the same composition ratio, the average particle size of the scale inhibitory effective ingredients in the outer layer structure is smaller than the average particle size of the scale inhibitory effective ingredients in the inner layer structure. This means that when the composition of the outer layer structure and the inner layer structure is the same, the overall particle size of the scale inhibitory effective ingredients in the outer layer structure is smaller than the overall particle size of the scale inhibitory effective ingredients in the inner layer structure. Here, the average particle size is used as a measurement standard. There may be a situation where the particle size of the larger particle size of the scale inhibitory effective ingredients in the outer layer structure is greater than or equal to the particle size of the smaller particle size of the scale inhibitory effective ingredients in the inner layer structure. No specific limitation is made here.

[0061] In the scale inhibition material provided in the embodiment of the present application, the scale inhibition material is arranged as a multilayer structure which is stacked in sequence from the inside to the outside along the radial direction of the columnar particles, the first layer structure is columnar, and the remaining layers are annular structures. When it is used for scale inhibition, the scale inhibition effective ingredients are soluble in water, and because the mass proportion of the scale inhibition effective ingredients in each layer structure is greater than or equal to 45%, therefore, as the scale inhibition effective ingredients dissolve, the polymer substrate will be peeled off and dissolved in the water. Therefore, the effective scale inhibitors in each layer structure of the scale inhibitor material can be released at a certain speed under the dissolution of the scale inhibitor material, and as the scale inhibitor material is dissolved and consumed, the specific surface area to volume ratio of the scale inhibitor material becomes larger and larger. At this time, since in the radial direction gradually away from the first layer structure, in any two adjacent layers, at the same composition ratio, the average particle size of the effective scale inhibitor components of the outer layer structure is smaller than the average particle size of the effective scale inhibitor components of the inner layer structure, therefore, as the scale inhibitor material is dissolved and consumed, the average particle size of the effective scale inhibitor components of the scale inhibitor material becomes larger, thereby effectively reducing the release rate of the effective scale inhibitor components, and then effectively balancing the release rates of the effective scale inhibitor components in the early and late use of the scale inhibitor material, so that the effective scale inhibitor components in the scale inhibitor material can be released smoothly in the early and late use, solving the problems of insufficient early scale inhibition efficiency, excessively high late scale inhibition efficiency and excessive consumption speed of the complex type scale inhibitor material in the related art, thereby solving the problems of difficult to effectively control the release speed of the effective scale inhibitor components of the complex type scale inhibitor material in the related art, and broadening the scope of use and application scenarios of the complex type scale inhibitor material.

[0062] There is no limitation on the specific selection of the antiscaling effective component.

[0063] In some embodiments, the antiscaling active ingredient includes calcium polyphosphate and polycarboxylate zinc powder dispersed in the calcium polyphosphate.

[0064] Calcium polyphosphate is an inorganic polymer that is polymerized from calcium phosphate units. The basic unit of its chemical structure is calcium phosphate, and multiple calcium phosphate units are connected together through oxygen atoms in the phosphate group to form a long chain or network polymer structure. From a chemical formula point of view, it can be expressed as (CaP2O6) n In the form of, n represents the degree of polymerization, indicating the number of repetitions of the calcium phosphate unit.

[0065] At the same time, calcium polyphosphate has good biocompatibility. It can interact with human tissues without causing obvious immune responses and is often used in the repair and regeneration of bone tissue.

[0066] Zinc polycarboxylate is an organic metal compound mainly composed of polycarboxylic acid groups and zinc ions. Polycarboxylic acid groups are usually long chain structures formed by polymerization of carboxyl-containing monomers. These carboxyl groups can partially or completely react with zinc ions to form a stable polymer-metal ion complex. From the perspective of molecular structure, it is a three-dimensional network structure, in which the polycarboxylic acid chain serves as the main framework, and the zinc ions are distributed between the chains or at the nodes of the chains, playing the role of cross-linking and stabilizing the structure.

[0067] At the same time, zinc polycarboxylate is used as a bonding agent in dental materials to firmly bond tooth tissue and restorative materials together. It not only has good biocompatibility but also has antibacterial effects.

[0068] In these embodiments, a mixed material of calcium polyphosphate and zinc polycarboxylate powder is used as an effective scale inhibitor. On the one hand, the calcium polyphosphate is slightly soluble in water. Therefore, during the dissolution of the scale inhibitor material, the calcium polyphosphate can release phosphorus-containing groups having active carboxyl and hydroxyl groups in water to complex with calcium and magnesium ions in the water to form a water-soluble complex, thereby achieving a scale inhibition function. On the other hand, the zinc polycarboxylate powder is slightly soluble in water. Similar to calcium polyphosphate, during the dissolution of the scale inhibitor material, the zinc polycarboxylate powder can release zinc ions into water, thereby inhibiting the growth of bacteria in the water. On the other hand, the calcium polyphosphate and zinc polycarboxylate powder have good biocompatibility, which can further broaden the use scope and application scenarios of the scale inhibitor material. For example, the scale inhibitor material can be used in scale inhibition and purification of water bodies with relatively high requirements for toxicity and bacteria.

[0069] In some embodiments, the antiscaling material satisfies at least one of the following conditions:

[0070] (1) The materials for preparing the polymer substrate include: PE;

[0071] (2) In each layer structure, the mass proportion of the polymer substrate is 42% to 55%, the mass proportion of the polycarboxylate zinc powder is 10% to 20%, and the balance is calcium polyphosphate;

[0072] (3) The average particle size of the polycarboxylate zinc powder is 15 μm~25 μm.

[0073] In these embodiments, PE material is a commonly used adhesive for food packaging and water filter elements, and also has good biocompatibility, which can further enable the scale-inhibiting material to be used in water scale-inhibiting and purification scenarios with relatively high requirements for toxicity and bacteria. By limiting the mass proportions of the polymer base, calcium polyphosphate and polycarboxylate zinc powder in the scale-inhibiting material to the above range, on the one hand, it is convenient for the processing and molding of the scale-inhibiting material; on the other hand, it can provide sufficient scale-inhibiting effective ingredients for water scale-inhibiting and sterilization purification, thereby improving the scale-inhibiting rate and antibacterial rate of the scale-inhibiting material. By limiting the average particle size of the polycarboxylate zinc powder to 15μm~25μm, the dissolution and release rate of the polycarboxylate zinc powder in the water body can be further adjusted, thereby improving the sterilization stability and sterilization effect of the scale-inhibiting material in the water body.

[0074] In some embodiments, the columnar particles may include two or more layers of structure, such as the columnar particles may include four, five, or even seven or eight layers of structure, which is not specifically limited herein.

[0075] In some embodiments, the columnar particles include: a first columnar structure, a first annular structure, and a second annular structure stacked in sequence along the radial direction thereof, wherein the first annular structure is coated on the circumference of the first columnar structure, and the second annular structure is coated on the circumference of the first annular structure. At this time, in the first columnar structure, the average particle size of the scale-inhibiting effective component is 70 μm to 75 μm, in the first annular structure, the average particle size of the scale-inhibiting effective component is 60 μm to 65 μm, and in the second annular structure, the average particle size of the scale-inhibiting effective component is 50 μm to 55 μm.

[0076] In these embodiments, the antiscaling active ingredients in the antiscaling material can be released smoothly in different layer structures, thereby improving the antiscaling effect.

[0077] In some embodiments, the columnar particles are cylindrical, the diameter of the first columnar structure is 1.1 mm to 1.5 mm, the thickness of the first annular structure is 0.1 mm to 0.15 mm, and the thickness of the second annular structure is 0.1 mm to 0.15 mm.

[0078] In these embodiments, when the diameter of the first columnar structure is 1.1 mm, the thickness of the first annular structure may be 0.1 mm or 0.15 mm, and the outer diameter of the first annular structure may be 1.3 mm or 1.4 mm, respectively; when the diameter of the first columnar structure is 1.2 mm, the thickness of the first annular structure may be 0.1 mm or 0.15 mm, and the outer diameter of the first annular structure may be 1.4 mm or 1.5 mm, respectively; and so on; when the diameter of the first columnar structure is 1.3 mm, the outer diameter of the first annular structure may be 1.5 mm or 1.6 mm; when the diameter of the first columnar structure is 1.4 mm, the outer diameter of the first annular structure may be 1.6 mm or 1.7 mm; and when the diameter of the first columnar structure is 1.5 mm, the outer diameter of the first annular structure may be 1.7 mm or 1.8 mm.

[0079] Similar to the above-mentioned first annular structure, the outer diameter of the second annular structure can be calculated by calculating the outer diameter of the first annular structure and the thickness of the second annular structure.

[0080] For example, when the outer diameter of the first annular structure is 1.3 mm, the outer diameter of the second annular structure may be 1.5 mm or 1.6 mm, when the outer diameter of the first annular structure is 1.4 mm, the outer diameter of the second annular structure may be 1.6 mm or 1.7 mm, when the outer diameter of the first annular structure is 1.5 mm, the outer diameter of the second annular structure may be 1.7 mm or 1.8 mm, when the outer diameter of the first annular structure is 1.6 mm, the outer diameter of the second annular structure may be 1.8 mm or 1.9 mm, when the outer diameter of the first annular structure is 1.7 mm, the outer diameter of the second annular structure may be 1.9 mm or 2.0 mm, and when the outer diameter of the first annular structure is 1.8 mm, the outer diameter of the second annular structure may be 2.0 mm or 2.1 mm.

[0081] In some embodiments, the diameter of the first columnar structure is 1.3 mm, the outer diameter of the first annular structure is 1.6 mm, and the outer diameter of the second annular structure is 1.9 mm.

[0082] In these embodiments, the release rate and stability of the antiscaling active ingredients in the antiscaling material can be controlled within a more optimal range.

[0083] In some embodiments, in the first columnar structure, the first annular structure, and the second annular structure, the weight percentage of the zinc polycarboxylate powder is 11.3%, the weight percentage of the calcium polyphosphate is 44.3%, and the weight percentage of the polymer substrate is 44.4%; or,

[0084] In the first columnar structure, the first annular structure, and the second annular structure, the mass proportion of the polycarboxylate zinc powder is 19.6%, the mass proportion of the calcium polyphosphate is 37.8%, and the mass proportion of the polymer substrate is 42.6%; or,

[0085] In the first columnar structure, the first annular structure, and the second annular structure, the mass proportion of the polycarboxylate zinc powder is 10.5%, the mass proportion of the calcium polyphosphate is 36.4%, and the mass proportion of the polymer substrate is 53.1%; or,

[0086] In the first columnar structure, the first annular structure, and the second annular structure, the mass proportion of the polycarboxylate zinc powder is 14.5%, the mass proportion of the calcium polyphosphate is 38.0%, and the mass proportion of the polymer substrate is 47.5%.

[0087] In these embodiments, the antiscaling materials have good phosphorus dissolution stability, and the processing and molding effect of the antiscaling materials is good, and the antiscaling rate and antibacterial rate are higher.

[0088] Phosphorus dissolution stability is used to characterize the change in phosphorus dissolution amount. During the entire dissolution process of the scale inhibitor, the greater the change in phosphorus dissolution amount over time, the worse the phosphorus dissolution stability, and vice versa.

[0089] In a second aspect, some embodiments of the present application provide a method for preparing a scale inhibition material, such as Figure 1 As shown, the preparation method includes the following steps S11-S12:

[0090] S11, preparing a plurality of raw materials for scale-inhibiting materials; each raw material for scale-inhibiting materials is a mixture of polymer-based granules and scale-inhibiting effective ingredients, the polymer base and the scale-inhibiting effective ingredients are soluble in water, the scale-inhibiting effective ingredients are in powder form, and at the same composition ratio, the average particle sizes of the scale-inhibiting effective ingredients in any two raw materials for scale-inhibiting materials are different from each other;

[0091] The polymer substrate and the scale-inhibiting active ingredient are soluble in water, which means that after a plurality of scale-inhibiting materials are prepared into a scale-inhibiting material using raw materials, the scale-inhibiting material can be dissolved in water, so that the scale-inhibiting active ingredient in the scale-inhibiting material can be continuously released into the water, and the calcium ions in the water are complexed, so as to play a scale-inhibiting role. The scale-inhibiting active ingredient can exemplarily include a complexing scale-inhibiting material.

[0092] Under the same composition ratio, the average particle sizes of the anti-scaling active ingredients in any two portions of the anti-scaling material raw materials are different from each other. The explanation of the average particle size can be referred to the above description and will not be repeated here.

[0093] S12. Add multiple portions of raw materials for scale inhibition materials into different chambers of a multilayer extruder according to the different average particle sizes of their respective scale inhibition effective components, and prepare columnar particles by co-extrusion and cutting; along the radial direction of the columnar particles, the columnar particles include a multilayer structure stacked in sequence from the inside to the outside; in the multilayer structure, the first layer structure is columnar, and the remaining layers are annular structures, and the latter layer structure is coated on the circumference of the former layer structure; in the radial direction gradually away from the first layer structure, in any two adjacent layer structures, the average particle size of the scale inhibition effective component of the outer layer structure is smaller than the average particle size of the scale inhibition effective component of the inner layer structure.

[0094] In the preparation method of the scale-inhibiting material provided in the embodiment of the present application, a plurality of raw materials for scale-inhibiting materials are added into different chambers of a multilayer extruder according to the different average particle sizes of their respective effective scale-inhibiting ingredients, and the plurality of raw materials for scale-inhibiting materials are mixed, melted and extruded through different heating chambers by using a multilayer extruder, so that a scale-inhibiting material with a multilayer structure can be obtained. By adjusting the feeding chambers for the plurality of raw materials for scale-inhibiting materials, a multilayer structure can be obtained in which the average particle size of the effective scale-inhibiting ingredients is arranged from large to small from inside to outside. When the multilayer structure is used, the average particle size of the effective scale-inhibiting ingredients in the scale-inhibiting material is increased as the specific surface area to volume ratio of the scale-inhibiting material dissolves. It is set so that as the solubility increases, the release rate of the effective scale inhibitor in the early stage can be effectively increased while the release rate of the effective scale inhibitor in the later stage can be reduced, thereby effectively balancing the release rates of the effective scale inhibitor in the early stage and the later stage of the scale inhibitor material, so that the effective scale inhibitor in the scale inhibitor material can be released smoothly in the early stage and the later stage of use, solving the problems of insufficient scale inhibition efficiency in the early stage and too high scale inhibition efficiency and too fast consumption rate in the later stage of the complex type scale inhibitor in the related technology, thereby solving the problems of difficult to effectively control the release speed of the effective scale inhibitor in the complex type scale inhibitor in the related technology, and broadening the use scope and application scenarios of the complex type scale inhibitor.

[0095] In some embodiments, the multilayer extruder includes a plurality of heating chambers, wherein the outlet of the first heating chamber is cylindrical, the outlets of the remaining heating chambers are coaxially arranged with the outlet of the first heating chamber, and the outlet of the subsequent heating chamber is arranged around the outlet of the previous heating chamber; S12, comprising:

[0096] Adding multiple scale-inhibiting raw materials into a plurality of heating chambers arranged in sequence from the first heating chamber of a multilayer extruder according to the average particle sizes of their respective scale-inhibiting effective components in descending order, and co-extruding the molten materials in each heating chamber through the screw in each heating chamber, and obtaining a strip material after cooling;

[0097] The strip material is cut into sections along the length direction of the strip material to obtain columnar particles.

[0098] In these embodiments, multiple portions of raw materials for scale inhibition materials are added into a plurality of heating chambers arranged in sequence starting from the first heating chamber of a multilayer extruder in order of the average particle size of their respective effective scale inhibition ingredients from large to small. Since the outlet of the first heating chamber is columnar, the outlets of the remaining heating chambers are coaxially arranged with the outlet of the first heating chamber, and the outlet of the latter heating chamber is arranged around the outlet of the former heating chamber. Therefore, after the raw materials for scale inhibition materials in each heating chamber are heated to melt, the molten materials in each heating chamber are co-extruded by the screws in each heating chamber, so that a multilayer strip structure in which the average particle size of the effective scale inhibition ingredients is arranged from large to small from the inside to the outside can be obtained, and the columnar particles of the multilayer structure can be obtained by segmentally cutting the multilayer strip structure along the length direction of the multilayer strip structure.

[0099] In some embodiments, the co-extrusion temperature may be 140°C to 230°C.

[0100] In some embodiments, the columnar particles may be cylinders, the diameter of the cylinders may be 1.9 mm to 2.2 mm, and the height may be 9.8 mm to 10.2 mm.

[0101] In these embodiments, when the columnar particle comprises a first columnar structure, a first annular structure, and a second annular structure, the diameter of the cylinder is equal to the outer diameter of the second annular structure.

[0102] In some embodiments, S11 includes:

[0103] S111, preparing calcium polyphosphate monomer;

[0104] S112, mixing calcium polyphosphate monomer and polycarboxylate zinc powder and subjecting the mixture to sintering treatment, so that the calcium polyphosphate monomer is copolymerized to obtain a block polymer, and the polycarboxylate zinc powder is dispersed in the block polymer;

[0105] S113, crushing the block polymer into a plurality of powdered anti-scaling active ingredients, wherein the average particle sizes of any two powdered anti-scaling active ingredients are different from each other;

[0106] S114, mixing a plurality of powdered antiscaling active ingredients with a plurality of polymer-based granules contained in a plurality of raw materials for antiscaling materials, respectively, to prepare a plurality of raw materials for antiscaling materials.

[0107] In these embodiments, calcium polyphosphate monomers and zinc polycarboxylate powders are mixed and copolymerized by sintering to obtain calcium polyphosphate block polymers, and zinc polycarboxylate powders are dispersed in the block polymers. Then, the block polymers are crushed to obtain scale-inhibiting active ingredients with uniform composition but different average particle sizes. Multiple scale-inhibiting active ingredients with different average particle sizes are mixed with polymer-based pellets contained in multiple scale-inhibiting material raw materials to prepare multiple scale-inhibiting active ingredients with the same composition ratio but different average particle sizes.

[0108] In some embodiments, S111, preparing a calcium polyphosphate monomer, may include:

[0109] preparing an aqueous phosphoric acid solution;

[0110] Mixing calcium hydroxide and water to prepare a suspension of calcium hydroxide;

[0111] Slowly add the phosphoric acid aqueous solution to the calcium hydroxide suspension while stirring until the pH value of the liquid is 2-2.5;

[0112] The mixed liquid with a pH value of 2 to 2.5 is reacted at a constant temperature of 60° C. to 90° C. for 0.5 h to 3 h to precipitate solid calcium polyphosphate monomer, and then the solid calcium polyphosphate monomer is separated from the solution by a centrifuge to obtain calcium polyphosphate monomer.

[0113] The preparation of the phosphoric acid aqueous solution may include: mixing phosphoric acid and water and heating to prepare the phosphoric acid aqueous solution, wherein the mass percentage of phosphoric acid in the phosphoric acid aqueous solution may be 60% to 80%, and the heating temperature may be 60° C. to 90° C.

[0114] In some embodiments, in the above suspension, the mass percentage of calcium hydroxide can be 20%~30%, and the temperature of the suspension can be 60℃~90℃.

[0115] In some embodiments, in S112 , the particle size of the zinc polycarboxylate powder may be 15 μm to 25 μm.

[0116] In some embodiments, in S113 , the sintering process may be performed at a temperature of 800° C. to 850° C. and for a time of 20 h to 25 h.

[0117] In these embodiments, the degree of polymerization of calcium polyphosphate can be effectively increased, thereby increasing the molecular weight of calcium polyphosphate to reduce solubility and improve sustained-release performance.

[0118] In some embodiments, in S114 , the average particle size of the polymer substrate particles is 20 μm to 25 μm.

[0119] In order to objectively evaluate the technical effects of the embodiments of the present application, the present application will be described in detail and exemplarily through the following embodiments and comparative examples.

[0120] In the following examples and comparative examples, all raw materials can be purchased commercially, and in order to maintain the reliability of the experiment, the raw materials used in the following examples and comparative examples have the same physical and chemical parameters or are prepared by the same processing method.

[0121] Example 1

[0122] Example 1 provides a scale-inhibiting material, and the preparation method of the scale-inhibiting material is as follows:

[0123] (1) Preheat a 70% phosphoric acid aqueous solution to 80°C.

[0124] (2) Calcium hydroxide and water are mixed evenly to form a suspension having a calcium hydroxide mass percentage of 25%, and the temperature of the suspension is maintained at 80°C.

[0125] (3) Slowly add the phosphoric acid aqueous solution prepared in step (1) to the calcium hydroxide suspension prepared in step (2), stirring while adding, until the pH value of the liquid reaches 2.3.

[0126] (4) The mixed liquid in step (3) is reacted at 80° C. for 2 h to precipitate solid calcium polyphosphate monomer, and the solid calcium polyphosphate monomer is separated from the solution by a centrifuge for later use.

[0127] (5) The solid calcium polyphosphate monomer prepared in step (4) and the polycarboxylate zinc powder with an average particle size of 20 μm are uniformly mixed in a mass ratio of 44.3:11.3, and then sintered at 820° C. for 22 h to obtain a block polymer material.

[0128] (6) The block polymer material prepared in step (5) is crushed into three polymer powders (i.e., antiscaling effective components) by a crushing device. The average particle sizes of the three antiscaling effective components are 52 μm, 62 μm, and 72 μm, respectively.

[0129] (7) The three anti-scaling active ingredients prepared in step (6) are mixed with PE micropowder with an average particle size of 22 μm in a mass ratio of 55.6:44.4, and extruded and cut through a three-layer hot extruder to form columnar particles with a diameter of 2 mm and a height of 10 mm; wherein the three-layer hot extruder comprises three heating chambers, wherein the outlet of the first heating chamber is columnar and has an inner diameter of 1.3 mm, the outlet of the second heating chamber and the outlet of the third heating chamber are both coaxially arranged with the outlet of the first heating chamber, and the outlet of the second heating chamber is arranged around the outlet of the first heating chamber and has an inner diameter of 1.6 mm, and the outlet of the third heating chamber is arranged around the outlet of the second heating chamber and has an inner diameter of 1.9 mm, and the extrusion temperature is 200°C.

[0130] Example 2

[0131] The preparation method of the scale-inhibiting material provided in Example 2 is substantially the same as the preparation method of the scale-inhibiting material provided in Example 1, except that:

[0132] In step (5), the mass ratio of the solid calcium polyphosphate monomer to the polycarboxylate zinc powder having an average particle size of 20 μm is 37.8:19.6;

[0133] In step (7), the mass ratio of the three anti-scaling active ingredients mixed with the PE micropowder with an average particle size of 22 μm is 57.4:42.6.

[0134] Example 3

[0135] The preparation method of the scale-inhibiting material provided in Example 3 is substantially the same as the preparation method of the scale-inhibiting material provided in Example 1, except that:

[0136] In step (5), the mass ratio of the solid calcium polyphosphate monomer to the polycarboxylate zinc powder having an average particle size of 20 μm is 36.4:10.5;

[0137] In step (7), the mass ratio of the three anti-scaling active ingredients mixed with the PE micropowder with an average particle size of 22 μm is 46.9:53.1.

[0138] Example 4

[0139] The preparation method of the scale-inhibiting material provided in Example 4 is substantially the same as the preparation method of the scale-inhibiting material provided in Example 1, except that:

[0140] In step (5), the mass ratio of the solid calcium polyphosphate monomer to the polycarboxylate zinc powder having an average particle size of 20 μm is 38.0:14.5;

[0141] In step (7), the mass ratio of the three anti-scaling active ingredients mixed with the PE micropowder with an average particle size of 22 μm is 52.5:47.5.

[0142] Example 5

[0143] The preparation method of the scale-inhibiting material provided in Example 5 is substantially the same as the preparation method of the scale-inhibiting material provided in Example 1, except that:

[0144] In step (5), the mass ratio of the solid calcium polyphosphate monomer to the polycarboxylate zinc powder having an average particle size of 20 μm is 35.2:21.2;

[0145] In step (7), the mass ratio of the three anti-scaling active ingredients mixed with the PE micropowder with an average particle size of 22 μm is 56.4:43.6.

[0146] Example 6

[0147] The preparation method of the scale-inhibiting material provided in Example 6 is substantially the same as the preparation method of the scale-inhibiting material provided in Example 1, except that:

[0148] In step (5), the mass ratio of the solid calcium polyphosphate monomer to the polycarboxylate zinc powder having an average particle size of 20 μm is 47.7:8.2;

[0149] In step (7), the mass ratio of the three anti-scaling active ingredients mixed with the PE micropowder with an average particle size of 22 μm is 55.9:44.1.

[0150] Example 7

[0151] The preparation method of the scale-inhibiting material provided in Example 7 is substantially the same as the preparation method of the scale-inhibiting material provided in Example 1, except that:

[0152] In step (5), the mass ratio of the solid calcium polyphosphate monomer to the polycarboxylate zinc powder having an average particle size of 20 μm is 43.2:18.9;

[0153] In step (7), the mass ratio of the three anti-scaling active ingredients to the PE micropowder with an average particle size of 22 μm is 62.1:37.9.

[0154] Example 8

[0155] The preparation method of the scale-inhibiting material provided in Example 8 is substantially the same as the preparation method of the scale-inhibiting material provided in Example 1, except that:

[0156] In step (5), the mass ratio of the solid calcium polyphosphate monomer to the polycarboxylate zinc powder having an average particle size of 20 μm is 33.2:10.4;

[0157] In step (7), the mass ratio of the three anti-scaling active ingredients to the PE micropowder with an average particle size of 22 μm is 43.6:56.4.

[0158] Comparative Example 1

[0159] The preparation method of the scale inhibitor material provided in Example 1 is basically the same as the preparation method of the scale inhibitor material provided in Example 1, except that:

[0160] In step (5), the mass ratio of the solid calcium polyphosphate monomer to the polycarboxylate zinc powder having an average particle size of 20 μm is 33.2:10.4;

[0161] In step (6), the block polymer material prepared in step (5) is crushed into a polymer powder with an average particle size of 62 μm by a crushing device, and the polymer powder is used as an effective antiscaling ingredient;

[0162] In step (7), the anti-scaling active ingredient prepared in step (6) is mixed with PE micropowder with an average particle size of 22 μm in a mass ratio of 43.6:56.4, and is extruded through a single-layer hot extruder and cut into columnar particles of the same size as in Example 1, that is, the single-layer hot extruder only includes one columnar outlet, and the inner diameter of the columnar outlet is 1.9 mm.

[0163] Test Case

[0164] 1. The phosphorus dissolution amount of the scale-inhibiting materials provided in Examples 1 to 8 and Comparative Example 1 was tested. The test method was as follows: water with a hardness of 320 mg / L and an alkalinity of 160 mg / L was used to conduct a water flow test at 40°C on a filter element equipped with 10 g of the scale-inhibiting material at a water flow rate of 4.4 L / min. A total of 48 tons of water was passed through the filter element, and a water sample was taken every 4 tons. The phosphorus dissolution amount in the test water samples of the scale-inhibiting materials provided in Examples 1 to 8 and Comparative Example 1 was tested by ICP component analysis. The change in the phosphorus dissolution amount in the test water samples of the scale-inhibiting materials provided in Example 1 and Comparative Example 1 during the entire water flow process is shown in FIG. Figure 2 shown.

[0165] Depend on Figure 2 It can be seen that the phosphorus dissolution amount of the scale-inhibiting material extruded by multiple layers during water flow is significantly more stable than that of the scale-inhibiting material extruded by single layer.

[0166] The square difference of the phosphorus dissolution amount measured in the test water samples of the scale inhibition materials provided in Examples 1 to 8 and Comparative Example 1 was taken to evaluate the stability of the phosphorus dissolution amount. The test results are shown in Table 1 below.

[0167] 2. The scale inhibition rate of the scale inhibition materials provided in Examples 1 to 8 and Comparative Example 1 was tested. The testing method was as follows: take 1L of test water with a total hardness of 700mg / L and a total alkalinity of 360mg / L, soak 10g of the scale inhibition material in it for 30 minutes, take out the supernatant as the scale inhibition water sample, and then test and calculate the scale inhibition rate of the scale inhibition materials provided in Examples 1 to 8 and Comparative Example 1 according to 8.0-9.0 in the calcium carbonate deposition method for determination of scale inhibition performance of water treatment agents in GB∕T16632-2019. The test results are shown in Table 1 below.

[0168] 3. The molding conditions of the scale-inhibiting materials provided in Examples 1 to 8 and Comparative Example 1 during the hot extrusion process were investigated. The results are shown in Table 1 below.

[0169] 4. The antibacterial rates of Staphylococcus aureus and Escherichia coli of the scale inhibition materials provided in Examples 1 to 8 and Comparative Example 1 were tested. The antibacterial test was performed according to the Chinese national standard GB / T 21510-2008 "Test Method for Antibacterial Performance of Nano-inorganic Materials".

[0170] Table 1

[0171]

[0172] As shown in Table 1, the phosphorus dissolution stability of the scale-inhibiting materials provided in Examples 1 to 6 and Example 8 of the present application is good, the square difference of the phosphorus dissolution is ≤3, the scale-inhibiting rate is high, which can reach more than 91.1%, and even more than 99%. In addition, the antibacterial rate of Staphylococcus aureus and the antibacterial rate of Escherichia coli can reach more than 99.5%, and have excellent antibacterial properties. However, due to the low content of PE powder in Example 7, the scale-inhibiting material failed in hot extrusion molding, and the scale-inhibiting material of the preset shape could not be prepared.

[0173] By comparing Examples 1 to 8, it can be seen that by controlling the mass proportion of the polymer base within the range of 42% to 55%, the mass proportion of the polycarboxylate zinc powder within the range of 10% to 20%, and the remainder being calcium polyphosphate, the scale inhibition material can be normally formed while maintaining a high scale inhibition rate, antibacterial rate against Staphylococcus aureus and antibacterial rate against Escherichia coli, and a high stability of phosphorus dissolution, thereby achieving excellent comprehensive performance.

[0174] Comparing Example 5 with Examples 1 to 4, it can be seen that when the content of zinc polycarboxylate powder is too high, the content of solid calcium polyphosphate monomer will be too low, thereby causing a decrease in scale inhibition rate.

[0175] Comparing Example 6 with Examples 1 to 4, it can be seen that when the content of the zinc polycarboxylate powder is too low, the antibacterial rates of Staphylococcus aureus and Escherichia coli are reduced.

[0176] Comparing Example 8 with Examples 1 to 4, it can be seen that when the PE powder content is too high, the solid calcium polyphosphate monomer content will be too low, thereby causing a decrease in the scale inhibition rate.

[0177] Comparison of Comparative Example 1 and Example 1 shows that the stability of phosphorus dissolution is greatly reduced by adopting the single-layer extrusion process.

[0178] In summary, the scale inhibitor material prepared by the preparation method of the scale inhibitor material provided in the embodiment of the present application has good properties (such as phosphorus dissolution stability, scale inhibition rate, antibacterial rate and extrusion moldability, etc.), which can make the scale inhibitor material have both good scale inhibition performance and antibacterial performance, and the raw materials have good biocompatibility, which can broaden the scope of use and application scenarios of the scale inhibitor material.

[0179] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0180] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.

Claims

1. A scale-inhibiting material, characterized in that: The anti-scaling material is a columnar particle, and the columnar particle has a multi-layer structure stacked in sequence from inside to outside along its radial direction; The first layer structure is columnar, and the remaining layers are annular structures, and the latter layer structure is wrapped around the circumference of the former layer structure; Each layer structure includes: a polymer substrate and an anti-scaling effective component dispersed in the polymer substrate; Among them, the scale inhibitory effective ingredient is soluble in water, the mass proportion of the scale inhibitory effective ingredient in each layer structure is greater than or equal to 45%, the scale inhibitory effective ingredient is in powder form, and in the radial direction gradually away from the first layer structure, in any two adjacent layer structures, at the same composition ratio, the average particle size of the scale inhibitory effective ingredient in the outer layer structure is smaller than the average particle size of the scale inhibitory effective ingredient in the inner layer structure.

2. The scale-inhibiting material according to claim 1, characterized in that: The anti-scaling effective component comprises calcium polyphosphate and polycarboxylate zinc powder dispersed in the calcium polyphosphate.

3. The scale-inhibiting material according to claim 2, characterized in that: The antiscaling material satisfies at least one of the following conditions: (1) The materials for preparing the polymer substrate include: PE; (2) In each layer structure, the mass proportion of the polymer substrate is 42% to 55%, the mass proportion of the zinc polycarboxylate is 10% to 20%, and the balance is the calcium polyphosphate; (3) The average particle size of the polycarboxylate zinc powder is 15 μm to 25 μm.

4. The scale-inhibiting material according to claim 2 or 3, characterized in that: The columnar particles include: a first columnar structure, a first annular structure, and a second annular structure sequentially stacked along the radial direction thereof, wherein the first annular structure is coated on the circumference of the first columnar structure, and the second annular structure is coated on the circumference of the first annular structure; In the first columnar structure, the average particle size of the scale-inhibiting effective component is 70 μm to 75 μm, in the first annular structure, the average particle size of the scale-inhibiting effective component is 60 μm to 65 μm, and in the second annular structure, the average particle size of the scale-inhibiting effective component is 50 μm to 55 μm.

5. The scale-inhibiting material according to claim 4, characterized in that: The columnar particles are cylindrical, the diameter of the first columnar structure is 1.1 mm to 1.5 mm, the thickness of the first annular structure is 0.1 mm to 0.15 mm, and the thickness of the second annular structure is 0.1 mm to 0.15 mm; Optionally, the diameter of the first columnar structure is 1.3 mm, the outer diameter of the first annular structure is 1.6 mm, and the outer diameter of the second annular structure is 1.9 mm.

6. The scale-inhibiting material according to claim 4, characterized in that: In the first columnar structure, the first annular structure and the second annular structure, the mass proportion of the zinc polycarboxylate powder is 11.3%, the mass proportion of the calcium polyphosphate is 44.3%, and the mass proportion of the polymer substrate is 44.4%; or, In the first columnar structure, the first annular structure and the second annular structure, the mass proportion of the zinc polycarboxylate powder is 19.6%, the mass proportion of the calcium polyphosphate is 37.8%, and the mass proportion of the polymer substrate is 42.6%; or, In the first columnar structure, the first annular structure and the second annular structure, the mass proportion of the zinc polycarboxylate powder is 10.5%, the mass proportion of the calcium polyphosphate is 36.4%, and the mass proportion of the polymer substrate is 53.1%; or, In the first columnar structure, the first annular structure and the second annular structure, the mass proportion of the polycarboxylate zinc powder is 14.5%, the mass proportion of the calcium polyphosphate is 38.0%, and the mass proportion of the polymer substrate is 47.5%.

7. A method for preparing a scale inhibition material, characterized in that: include: S11, preparing a plurality of raw materials for scale inhibitors; each raw material for scale inhibitors is a mixture of polymer-based particles and effective scale inhibitor ingredients, the effective scale inhibitor ingredients are soluble in water, and the mass proportion of the effective scale inhibitor ingredients in each raw material for scale inhibitors is greater than or equal to 45%, the effective scale inhibitor ingredients are in powder form, and at the same composition ratio, the average particle sizes of the effective scale inhibitor ingredients in any two raw materials for scale inhibitors are different from each other; S12. Add multiple portions of raw materials for scale inhibition materials into different chambers of a multilayer extruder according to the different particle sizes of their respective scale inhibition effective ingredients, and prepare columnar particles by co-extrusion and cutting; along the radial direction of the columnar particles, the columnar particles include a multilayer structure stacked in sequence from the inside to the outside; in the multilayer structure, the first layer structure is columnar, and the remaining layers are annular structures, and the latter layer structure is coated on the circumference of the former layer structure; in the radial direction gradually away from the first layer structure, in any two adjacent layer structures, the average particle size of the scale inhibition effective ingredient of the outer layer structure is smaller than the average particle size of the scale inhibition effective ingredient of the inner layer structure.

8. The preparation method according to claim 7, characterized in that: The multilayer extruder comprises a plurality of heating chambers, wherein the outlet of the first heating chamber is cylindrical, the outlets of the remaining heating chambers are coaxially arranged with the outlet of the first heating chamber, and the outlet of the subsequent heating chamber is arranged around the outlet of the previous heating chamber; S12, comprising: Adding a plurality of raw materials for the scale-inhibiting material into a plurality of heating chambers arranged in sequence from the first heating chamber of the multilayer extruder according to the average particle sizes of the respective scale-inhibiting effective components from large to small, and co-extruding the molten materials in each heating chamber through the screw in each heating chamber, and obtaining a strip material after cooling; The strip material is cut into sections along the length direction of the strip material to obtain the columnar particles.

9. The preparation method according to claim 7, characterized in that: S11, including: preparing calcium polyphosphate monomer; The calcium polyphosphate monomer and the zinc polycarboxylate powder are mixed and sintered to copolymerize the calcium polyphosphate monomer to obtain a block polymer, wherein the zinc polycarboxylate powder is dispersed in the block polymer; The block polymer is crushed into a plurality of powdered anti-scaling active ingredients, wherein the average particle sizes of any two of the powdered anti-scaling active ingredients are different from each other; A plurality of the powdered antiscaling active ingredients are mixed with a plurality of granular materials of the polymer base contained in the raw material for the antiscaling material, respectively, to prepare a plurality of the raw materials for the antiscaling material.

10. The preparation method according to claim 9, characterized in that: The preparation method satisfies at least one of the following conditions: (1) The co-extrusion temperature is 140°C to 230°C; (2) The sintering process is performed at a temperature of 800°C to 850°C and for a time of 20h to 25h; (3) The average particle sizes of the plurality of powdered antiscaling active ingredients are 50 μm-55 μm, 60 μm-65 μm and 70 μm-75 μm respectively; (4) The average particle size of the polymer substrate particles is 20 μm to 25 μm.

Citation Information

Patent Citations

  • Composite slow-release solid scale inhibitor and preparation method thereof

    CN114195274A

  • Scale inhibitor particle, preparation method thereof and water heater

    CN118125633A

  • Water treatment material and production method thereof

    JP2017176898A

  • Scale inhibitor particle and preparation method therefor

    WO2020011174A1